Sintesis Hidroksiapatit Melalui Precipitated Calcium Carbonate (PCC) Cangkang Telur Ayam Ras Dengan Metode Presipitasi Pada Variasi Konsentrasi Pelarut HNO3 Dan Rasio CA/P - Qalbi, Tiffani; Azis, Yelmida; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Everyday, several thousand tons of eggshell are being generated as bio-waste in Indonesia. The eggshell is conteined 94% calcium carbonate (CaCO3) which can be used as raw material to synthesis hydroxyapatite (HAp). HAp is a bioactive ceramic material with high bioafinity and can be used as bone and dental implant. In this study, HAp was synthesized by precipitation method, using precipitated calcium carbonate (PCC) from chicken eggshell that has 99% purity. PCC as a calcium source was reacted with diamonium hydrogen phosphate ((NH4)2HPO4) as phosphorus source under concentration of HNO3 solvent (0,3; 0,4; 0,5 M) and Ca and P ratio varied from reactant (1,57; 1,67; 1,77) . The analysis using FTIR showed that the adsorption of PO43- and OH- ion in each sample indicated that the calcium phosphate compound has been formed. The sharpest peaks obtained on sample at the concentration of 0,4 M HNO3 solvent with ratio of Ca/P 1,57; a concentration of 0,4 M HNO3 solvent with ratio of Ca/P 1,67 and a concentration of 0,5 M HNO3 solvent with ratio of Ca/P 1,77. Based on XRD analysis, the best HAp obtained in concentration of 0,5 M HNO3 solvent and ratio of Ca/P 1,77 with crystal size 40.38 nm and crystal structure was hexagonal. The analysis by SEM-EDX showed that the morphology of HAp was agglomerates with single particles tends spherical and ratio of Ca/P was 1,5. The surface area of HAp obtained from the BET analysis was 3,606 m2/g and the yield was 58,89%.Keywords : Hydroxyapatite, precipitation method, PCC chicken egg shell, ratio Ca/P